Kemampuan Verbal Matematis dalam Menyelesaikan Soal Cerita Program Linier Pada Siswa Kelas XI IPA MAN 2 Kota Bima - Mutmainah Mutmainah; Arnasari Merdekawati H; Mutia Silmi (Griya Journal of Mathematics Education and Application, 2023)
This study aims to k now verbal ability in mathematical linear program solving word problems in class XI IPA MAN 2 Kota Bima spread over 5 classes. The subject determination technique used purposive sampling with a total of 52 students out of a total of 211 students. The criteria for determining the subject with the following considerations: 1) Students have received learning about linear programming; 2) Students have potential verbal abilities which are assessed based on the results of the verbal ability test in the linear program as a requirement in determining the subject group. The analysis technique in this study uses descriptive analysis. Based on the results of the study, it was found that the level of mathematical verbal ability in solving story problems in the linear program of class XI IPA MAN 2 Kota Bima was in the medium category. Students' mathematical verbal ability shows that the higher the level of students' verbal ability, the easier it is for students to understand and solve math problems or questions with the right answers.